Assessing the stability of psychobiological stress reactivity during adolescence: mixed-effect modelling of cortisol responses to laboratory stressors [version 2; peer review: 2 approved] - Elizabeth Susman; Jen O'Shea; Samantha Dockray (HRB Open Research)
Background Puberty has been historically considered as a time of risk and vulnerability for young people. It is associated with rapid development in the hypothalamus, which is central in the production of both stress and sex steroids. While patterns of stress reactivity are calibrated in early life, this time of rapid development may provide a means for these patterns to change. This purpose of this study was to examine whether patterns of cortisol reactivity remained stable across one year of pubertal development, and whether variations in pubertal development impacted on this stability. Methods This study used a secondary dataset comprised of 102 adolescent-aged children and adolescents. Children and adolescents took part in the Trier Social Stress Test to elicit a physiological stress response. Cortisol reactivity was measured as the increase in salivary cortisol concentration taken at five time points throughout the session. Pubertal stage was measured by nurse report where possible, and parent/self-report otherwise and was used to calculate pubertal timing and tempo relative to peers. Measures of anxiety, BMI, and socio-economic status were taken and included in analysis. Results Results of a linear mixed-effect model found there to be a significant difference in cortisol reactivity over time, indicating that cortisol stress reactivity did not remain stable during this time (Estimate= 3.39, t=3.67, p<.001, CI[1.56, 5.22]). Additionally, results show children and adolescents who developed slower/quicker than peers displayed decreased stress reactivity (Estimate= -3.59, t=-2.13. p=.03, CI[-6.92, -0.25]). Conclusions This research contributes to a relatively small but consistent body of research noting pattern of increased cortisol reactivity during pubertal development. While a significant effect was found for pubertal tempo, this finding should not be considered indicative of any true effect.